Mechanical response of human female breast skin under uniaxial stretching - Kumaraswamy, N. (J Mech Behav Biomed Mater, 2017)
Skin is a complex material covering the entire surface of the human body. Studying the mechanical properties of skin to calibrate a constitutive model is of great importance to many applications such as plastic or cosmetic surgery and treatment of skin-based diseases like decubitus ulcers. The main objective of the present study was to identify and calibrate an appropriate material constitutive model for skin and establish certain universal properties that are independent of patient-specific variability. We performed uniaxial tests performed on breast skin specimens freshly harvested during mastectomy. Two different constitutive models – one phenomenological and another microstructurally inspired – were used to interpret the mechanical responses observed in the experiments. Remarkably, we found that the model parameters that characterize dependence on previous maximum stretch (or preconditioning) exhibited specimen-independent universal behavior.